2019
DOI: 10.1177/1933719118765970
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenomics in IVF: A New Era in the Concept of Personalized Medicine

Abstract: Pharmacogenomics is a promising approach in the field of individualized medicine in in vitro fertilization (IVF) treatment that aims to develop optimized pharmacotherapy depending on the genetic background of each infertile woman, thus to ensure maximum effectiveness of the medication used, with minimal side effects. The unique genetic information of each infertile woman, in combination with already known, as well as new predictors of ovarian response and the progress of pharmacoepigenomics, is anticipated to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 115 publications
0
3
0
Order By: Relevance
“…Several studies have been reported in past on the same lines demonstrating the association of the genotype with less oocytes retrieved, lower follicle-to-oocyte index, more resistant to FSH action and requiring stronger stimulus. [ 20 21 22 ]…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been reported in past on the same lines demonstrating the association of the genotype with less oocytes retrieved, lower follicle-to-oocyte index, more resistant to FSH action and requiring stronger stimulus. [ 20 21 22 ]…”
Section: Discussionmentioning
confidence: 99%
“…Nonadherence behaviors during treatment in clinical trials compromise study power, reduce treatment effect size, and weaken overall study findings. In this era of popularity of personalized medicine, more research is focused on tailoring infertility pharmacotherapies to women based on their genetic characteristics to optimize treatment outcomes ( 69 ). Still, the benefits of these therapies are dependent upon women’s adherence to the regimen.…”
Section: Discussionmentioning
confidence: 99%
“…The potential of pharmacogenomics to introduce a new era in IVF treatment has recently been summarized (Kalinderi et al, 2019). Much remains to be explored further, but it is to be expected that additional genomic information generated from large data sets will give rise to much improved individualized infertility care.…”
Section: Ethnic and Biomarker Contextmentioning
confidence: 99%